Pengaruh Penerapan Asesmen Diagnostik Non-Kognitif Terhadap Motivasi Belajar Peserta Didik Pada Mata Pelajaran PAI Fase D - Salamudin, Ceceng; Sulistiani, Sulistiani (STAI Al-Musaddadiyah Garut, 2024)
Motivation is a crucial factor in Islamic Religious Education (PAI) learning activities; however, current phenomena indicate that the percentage of students' learning motivation is still below 50%. Given this fact, the low level of students' learning motivation can certainly hinder the learning process. Therefore, non-cognitive diagnostic assessment becomes one of the efforts to determine students' motivation levels at the beginning of the learning activities. This can help diagnose students' initial conditions, serving as a basis for developing lesson plans to be implemented in the classroom. This study aims to describe the impact of applying non-cognitive diagnostic assessment on students' learning motivation in PAI subject for Phase D at SMPN 1 Karangtengah Garut with the